2023
DOI: 10.1002/mar.21822
|View full text |Cite
|
Sign up to set email alerts
|

Embodiment, immersion, and enjoyment in virtual reality marketing experiences

Abstract: This experiential marketing study examines the effects of body position and embodiment in shaping consumer intentions mediated by immersion and enjoyment during a virtual reality experience. After a qualitative study (n = 13) aimed at understanding what, in a virtual reality experience, motivates individuals to want to consume the promoted offer, we conducted a quantitative study (n = 300), using a partial least squares structural equation model. Our experimental context placed the users in the role of a kayak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The salience of perceived enjoyment in shaping attitudes is particularly noteworthy. Rather than spotlighting solely the practical advantages of a VR device, marketers might find it more effective to underscore the sheer enjoyment and immersive experiences their product offers 134 . Imagining an advertisement campaign that vividly brings to life the exhilarating adventures, captivating landscapes, and thrilling narratives possible with a particular VR headset can be potent in influencing prospective buyers.…”
Section: Discussionmentioning
confidence: 99%
“…The salience of perceived enjoyment in shaping attitudes is particularly noteworthy. Rather than spotlighting solely the practical advantages of a VR device, marketers might find it more effective to underscore the sheer enjoyment and immersive experiences their product offers 134 . Imagining an advertisement campaign that vividly brings to life the exhilarating adventures, captivating landscapes, and thrilling narratives possible with a particular VR headset can be potent in influencing prospective buyers.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond narratives and arguments, researchers are interested in other message comparisons, such as the relative persuasive impact of augmented versus virtual reality (Leveau & Camus, 2023) and narrative versus statistical information (Allen & Preiss, 1997; Kopfman et al, 1998; Zebregs et al, 2015). Concerning the latter, all three cross‐modal pathways would seem to be viable for narratives and statistical information; however, researchers should also consider whether other pathways exist (Han & Fink, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In ESS, the use of VR in advertising may enhance key criteria used to quantify ad performance. Mileva (2022) observed that VR advertising had much higher levels of engagement and emotional intensity than traditional television advertising. Another study by Wang et al (2020) found that VR commercials were more effective than traditional video ads in increasing brand recall, brand identity, and purchase intent.…”
Section: Debatementioning
confidence: 99%